Sustentabilidade das edificações : do projeto à demolição - Leicht Neto, Eugênio Henrique (2011)
Sustainability as a new paradigm for the various areas of science and technology is the subject matter of this work. It investigates concepts and history related to sustainability and its impact on the construction supply chain, addressing the role of the professionals involved, covering from the architectural design to demolition or dismantling. Examples of sustainable construction in Brazil and abroad were placed. The author believes in sustainability as a process that requires the involvement of the whole society, contributing to the dialogue between the production and the environment. In this sense some concepts of sustainability-related construction process and property lifetime were applied proposing an architectural design for a residence in the metropolitan area of Recife